Corelation Between Level of Knowledge and Antibiotic Use Behaviour in Kelurahan Sei Putih Timur, Medan - KABAN, SRI MELINDA; Kumar, Ajith; Hafaz Zakky Abdillah; Anggrreiny; Siti Syarifah (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2025)
Background: Antibiotics are one of the great discoveries in the world of health that have saved many lives since their invention by Sir Henry Flaming in 1928. Not long after its discovery, antibiotic usage faced a new issue, which is antibiotic resistance that caused antibiotic effectivity to decrease and caused millions of deaths ever since. Until now, antibiotics have become a global threat that has to be solved. This research aims to determine the community’s knowledge level about antibiotics, if their use of antibiotics is rational, and if knowledge about antibiotics in the community will affect their usage of antibiotics. Method: A cross-sectional strategy is used in this descriptive-analytical study. The population and sample of this study were the community of Kelurahan Sei Putih Timur 2 Medan that met the criteria of respondents of 120 people.T Results and Discussion: The results obtained were 38 respondent (31.7%) has insufficient level of knowledge about antibiotics, 56 respondent (46.7%) has sufficient knowledge and 26 respondent (21.7%) has good knowledge about antibiotics. The number of respondent who has rational usage of antibiotics was 69 (57.5%) and the other 51 respondent (42.5%) has irrational usage of antibiotics. From analysis, 63 respondent, has sufficient to good knowledge about antibiotics and rational usage of it. Conclusion: Most of the antibiotic use behaviour of the East Sei Putih 2 Community is classified as rational, and has sufficient knowledge about antibiotics